(3v+4)(1+v)=0

Simple and best practice solution for (3v+4)(1+v)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3v+4)(1+v)=0 equation:


Simplifying
(3v + 4)(1 + v) = 0

Reorder the terms:
(4 + 3v)(1 + v) = 0

Multiply (4 + 3v) * (1 + v)
(4(1 + v) + 3v * (1 + v)) = 0
((1 * 4 + v * 4) + 3v * (1 + v)) = 0
((4 + 4v) + 3v * (1 + v)) = 0
(4 + 4v + (1 * 3v + v * 3v)) = 0
(4 + 4v + (3v + 3v2)) = 0

Combine like terms: 4v + 3v = 7v
(4 + 7v + 3v2) = 0

Solving
4 + 7v + 3v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(4 + 3v)(1 + v) = 0

Subproblem 1

Set the factor '(4 + 3v)' equal to zero and attempt to solve: Simplifying 4 + 3v = 0 Solving 4 + 3v = 0 Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3v = 0 + -4 3v = 0 + -4 Combine like terms: 0 + -4 = -4 3v = -4 Divide each side by '3'. v = -1.333333333 Simplifying v = -1.333333333

Subproblem 2

Set the factor '(1 + v)' equal to zero and attempt to solve: Simplifying 1 + v = 0 Solving 1 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + v = 0 + -1 Combine like terms: 1 + -1 = 0 0 + v = 0 + -1 v = 0 + -1 Combine like terms: 0 + -1 = -1 v = -1 Simplifying v = -1

Solution

v = {-1.333333333, -1}

See similar equations:

| 30b+(35)(300-b)=700 | | h(x)=x+x*2 | | 25p+50b=600 | | 100=(x+11)(x-5) | | a=(x+11)(x-5) | | -7x+4x+5=2 | | 3xy+x-y=1 | | 19+4(2c-3)= | | 100=2(x+11)(x-5) | | 4x+2z=4+3y | | -5x-9=-4x+1 | | -3x-15y-3x+8y= | | 2x+4=5x-x | | sec(x)sec(x)-7=0 | | sex^2(x)-7=0 | | 7x+(-3y)+(-8x)+9y= | | 3x+3(x-7)= | | 2x+5x+3=3-7x | | 5n-3(n-6)=2+3n | | (3x-6)2=36 | | 2x+3z=5+7y | | y^2=-7 | | 3(4y-1)=(5y+.5) | | 3/14/7/10 | | 5y+y=42 | | 5-y-y=15 | | 1/3w-9/5=-1/2 | | 2a+5-(a-7)= | | 4x^2+5(4x^2-x)-3x= | | (2535+-1157x+189x^2+x^3)(x+1.5)=0 | | 4b^2+20b+25= | | 4y+2w=7 |

Equations solver categories